Multi‐Year Statistics of LEO Energetic Electrons as Observed by the Korean NextSat‐1 - Jaeheung Park; Kyoung Wook Min; Hoonkyu Seo; Eo‐Jin Kim; Kwangsun Ryu; Jongdae Sohn; Jongho Seon; Ji‐Hyeon Yoo; Seunguk Lee; Brian Kress; Junchan Lee; Changho Woo; et al. (Space Weather)
Abstract Monitoring the Earth's radiation belt by Low‐Earth‐Orbit (LEO) satellites has a long history and complemented observations near the high‐altitude equatorial plane. However, most of the previous LEO missions suffered from limitations in energy resolution, energy range, L‐shell coverage, or the mission lifetime, which leave room for further improvement in this topic. For <80 keV electrons, the slot‐region outer edge at LEO moves inward with increasing geomagnetic activity, which agrees with previous Van Allen Probes reports. The behavior is more conspicuous for lower‐energy electrons. Latitudinal profiles of outer‐belt electron flux are smoother equatorward of the geosynchronous footprint latitudes (|MLAT| ∼ 66°) than poleward. The NextSat‐1 electron flux is positively correlated to geosynchronous observations, with the coefficient generally higher for higher electron energies. Also, both the geosynchronous and NextSat‐1 data exhibit similar spectral indices close to −3 in the log‐log space. All these results complement and expand previous knowledge on energetic electrons. The main findings are discussed in the context of existing literature.